Immense Potential of Ayurveda in Improving Dental Health: A Holistic Approach - Gupta, Ankita; Purohit, Abhishek (Journal of Orofacial Research, 2018)
There has been a change in thinking of the people across the world with a growing tendency towards “GO NATURAL” especially in the field of health sciences. Ayurveda is the ancient Indian system of health-care and longevity and should be considered as an alternative by integrating it with the modern dentistry. The present review aims to discuss various Ayurvedic plants and their significance in dentistry. Along with the PUBMED, MEDLINE, Medknow indexed journals, peer-reviewed and non-indexed journals were also reviewed using aloe vera, turmeric, honey, licorice, triphala and oral health as the keywords. The incorporation of Ayurveda into modern oral health-care practices will make dentistry much safer, affordable and more accessible for the lower socio-economic groups in society.